P72 Investigating the use of pre-exposure prophylaxis-a preliminary anonymous survey. (18th May 2015) - Bull, Lauren; Rayment, Michael; Phillips, Joe; McOwan, Alan
Abstract : Background: Pre-exposure prophylaxis (PrEP) has been proven to be biologically effective, and its clinical efficacy continues to be assessed in trials. Data have been published on patient's willingness to take PrEP, but we are unaware whether patients are already doing so outside of clinical trials and how they are sourcing the medication. Methods: A preliminary anonymous questionnaire was offered to HIV negative men who have sex with men (MSM) attending our services. The questionnaire sought to gain basic demographic data, the frequency of condomless sex in the preceding three months, whether participants had heard of PreP, whether they had taken it, and if so, how long for and how they sourced the medication. Results: 80 completed questionnaires were returned. The mean age was 30.6 years. The median number of partners in the last three months was 4 (range 1–55). 49% of respondents had 1–5 episodes of condomless sex in the preceding 3 months and 6% had >10 episodes of condomless sex. The majority of respondents (82%) had heard of PrEP. Five respondents (6%) had taken PrEP: one had been taking part in a clinical trial, three had used post-exposure prophylaxis as PrEP for between 24 and 28 days, and one had used a partner's anti retrovirals for 7 days. Discussion: This preliminary anonymous questionnaire suggests that the majority of HIV negative MSM attending our clinic have knowledge of PrEP. A small number are actively sourcing anti-retroviral medication to use as PrEP outside of clinical trials. We are now expanding this study to reach a higher proportion of our clinic attendees and also to link responses to clinic numbers in order to gain more behavioural information.